N-Glycoform Diversity of Cellobiohydrolase I from Penicillium decumbens and Synergism of Nonhydrolytic Glycoform in Cellulose Degradation - Gao, Le (American Society for Biochemistry and Molecular Biology, 2012)
Four cellobiohydrolase I (CBHI) glycoforms, namely, CBHI-A, CBHI-B, CBHI-C, and CBHI-D, were purified from the cultured broth of Penicillium decumbens JU-A10. All glycoforms had the same amino acid sequence but displayed different characteristics and biological functions. The effects of the N-glycans of the glycoforms on CBH activity were analyzed using mass spectrum data. Longer N-glycan chains at the Asn-137 of CBHI increased CBH activity. After the N-glycans were removed using site-directed mutagenesis and homologous expression in P. decumbens, the specific CBH activity of the recombinant CBHI without N-glycosylation increased by 65% compared with the wild-type CBHI with the highest specific activity. However, the activity was not stable. Only the N-glycosylation at Asn-137 can improve CBH activity by 40%. rCBHI with N-glycosylation only at Asn-470 exhibited no enzymatic activity. CBH activity was affected whether or not the protein was glycosylated, together with the N-glycosylation site and N-glycan structure. N-Glycosylation not only affects CBH activity but may also bring a new feature to a nonhydrolytic CBHI glycoform (CBHI-A). By supplementing CBHI-A to different commercial cellulase preparations, the glucose yield of lignocellulose hydrolysis increased by >20%. After treatment with a low dose (5 mg/g substrate) of CBHI-A at 50 °C for 7 days, the hydrogen-bond intensity and crystalline degree of cotton fibers decreased by 17 and 34%, respectively. These results may provide new guidelines for cellulase engineering.